2003
DOI: 10.1002/eat.10146
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic investigation of pericardial effusion in a case of anorexia nervosa

Abstract: Pericardial effusion has recently been reported as a complication of anorexia nervosa. A distinct pathophysiological cause of it could not be revealed. In some reports, there was a probable correlation between weight gain and reduction of pericardial effusion in anorexia nervosa cases. We encountered a case in which pericardial effusion remitted completely along with body weight increase and normalization of low T3 syndrome. These findings suggest that the reduction of pericardial effusion may correlate with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 5 publications
1
12
0
3
Order By: Relevance
“…One study observed that pericardial effusion remitted with weight gain and normalization of serum T3 levels. 2 This was corroborated by a more recent study of 173 adolescent patients with AN. 3 They found that 35% of patients had a pericardial effusion; in contrast no control patients had evidence of pericardial effusion.…”
Section: Structural Complicationsmentioning
confidence: 59%
See 1 more Smart Citation
“…One study observed that pericardial effusion remitted with weight gain and normalization of serum T3 levels. 2 This was corroborated by a more recent study of 173 adolescent patients with AN. 3 They found that 35% of patients had a pericardial effusion; in contrast no control patients had evidence of pericardial effusion.…”
Section: Structural Complicationsmentioning
confidence: 59%
“…The etiology of pericardial effusion in AN is uncertain. One study observed that pericardial effusion remitted with weight gain and normalization of serum T3 levels . This was corroborated by a more recent study of 173 adolescent patients with AN .…”
Section: Methodsmentioning
confidence: 69%
“…Inagaki et al 8 found increased plasma levels of BNP in a patient with anorexia nervosa and pericardial effusion. Plasma BNP decreased as pericardial effusion remitted.…”
Section: Resultsmentioning
confidence: 98%
“…In clinical practice, patients with similar or even lower BMI are currently seen without cardiac involvement. An association of low T 3 syndrome and pericardial effusion has been hypothesized, 8 with both changes disappearing completely after body weight increase; thus, low T 3 syndrome and pericardial effusion could be independently related to the anorectic condition. Other common causes of pericardial effusion, such as acute pericarditis of infectious origin, can also be excluded in this patient.…”
Section: Resultsmentioning
confidence: 99%
“…Atrial fibrillation was not detected. Pericardial effusion and elevated NT-proBNP levels have been suspected to be linked in AN [18]. Still, in our case, pericardial effusion was ruled out by both echocardiography and cardiac MRI.…”
Section: Discussionmentioning
confidence: 86%